Evaluation of unexpected protecting group removal in solid‐phase peptide synthesis: Quantified using continuous flow methods - Laude, Victoire; Nuño, Manuel; Moses, Roger C.; Guthrie, Duncan (Journal of peptide science, 2022)
As peptides gained interest as new drugs in the past years, their synthetic routes had been the subject of review and improvement. Fmoc/tBu‐based solid‐phase peptide synthesis (SPPS) is the most convenient technique, and the implementation in continuous flow has allowed for single‐pass coupling and deprotection reactions. The focus of this research is to evaluate the relationship between undesired solvent‐promoted reactions and final crude purity, by studying volume changes of a variable bed flow reactor through the synthesis. Based on the temperature, typical solvents for SPPS such as dimethylformamide (DMF) or N‐methyl‐2‐pyrrolidone (NMP) can cause unwanted Fmoc removal during wash steps. It was found that for every millilitre of DMF used at 80°C, up to 1 μmol of Fmoc‐protected peptide is deprotected, leading to additional impurities. This effect can, however, be minimised by adding additives such as HOBt, which reduces such unwanted deprotection to just 0.1 μmol/ml. Fmoc/tBu‐based solid‐phase peptide synthesis is a convenient technique. In continuous‐flow mode, it allows for single‐pass coupling and deprotection reactions. Here, the relationship between undesired solvent‐promoted reactions and final crude purity is evaluated, by studying volume changes of a variable bed flow reactor during the synthesis.